If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-88=4m+3(1+3m)
We simplify the equation to the form, which is simple to understand
-88=4m+3(1+3m)
Reorder the terms in parentheses
-88=4m+(+3+9m)
Remove unnecessary parentheses
-88=+4m+3+9m
We move all terms containing m to the left and all other terms to the right.
-4m-9m=+3+88
We simplify left and right side of the equation.
-13m=+91
We divide both sides of the equation by -13 to get m.
m=-7
| F(x)=x^2-4x-45 | | 22+12n=26 | | 4f=32 | | 2x(-3)=11 | | y-2.7=130.2 | | r-397=4 | | -4x-4=-7(x+2) | | 10=5y+10y | | k+6=(k-4)x(k+6) | | 11-4(n)=3 | | 79+q=613 | | 0.16x^2-0.24x+0.09=0 | | 801+p=910 | | 4x-3=2(2x+1) | | 11-4xn=3 | | x^2(x^2+15)=250 | | o-327=102 | | -y-6+2y=12 | | 425+n=480 | | m+61=80 | | l-49=98 | | 23+k=101 | | 4(t+11)=6(t-19) | | 5ln(5x+8)=22 | | 6x+3r-x+9=33 | | 47+j=93 | | 27+i=100 | | 80=x(x+2) | | h-17=40 | | 5+4y=1 | | g-80=42 | | 490+4x=(700+x)1.80 |